Interactions between Brain-Derived Neurotrophic Factor Val66Met Genotype and Sex Affect Hippocampal Regional Cerebral Blood Flow during Rest - Wei, S-M; Padmanabhan, A; Kohn, P.D.; Kolachana, B; Weinberger, D.R.; Berman, K.F. (NeuroImage (Orlando, Fla.), 2009)
Introduction The val66met single nucleotide polymorphism (SNP) in the human brain-derived neurotrophic factor (BDNF) gene influences hippocampal function, with the met allele being associated with abnormal hippocampal recruitment during episodic1 and working2 memory. Because BDNF and gonadal steroid hormones affect common molecular pathways and neural systems3, we sought to elucidate the effect of the BDNF val66met polymorphism as it interacts with sex on basal hippocampal function. A significant genotype by gender interaction in the functional connectivity analysis suggests that cross-hemisphere, inter-hippocampal functional cooperativity is most robust in male val homozygotes. Since the hippocampus is highly involved in the default-mode network4, processes mediated by the network could be co-monitored by sex differences and BDNF allelic variation.